A Preliminary Study of Tinted Film from Onion Peel - Siti Nursyakirah Idris,; Siti Amira Othman,; Fong Chui Nee,; Nur Amirah Elias,; Nur ‘Izqa Ashiqin Mohd Najib, (Multidisciplinary Applied Research and Innovation, 2023)
This study covers Polyethylene Terephthalate (PET) which is used as a raw material in the manufacture of tinted films which are mostly used in the processing industry. Malaysia's hot and humid conditions have made the tinted film an option for the majority of vehicle owners. This is because the tinted film can affect the temperature drop in vehicles or motorcyclists who use helmets. It can also minimize sunlight or light from outside that can interfere with the comfort and focus of road users. Moreover, with the advancement of technology nowadays, most of the natural materials that were originally used as materials in manufacturing are modified using synthetic materials. However, the move is seen as one of the causes of environmental pollution due to the chemicals it contains. Therefore, natural dyes will be used in this study as a measure to reduce the use of chemicals in universal life. This natural dye will determine whether the tinted film produced can comply with safety standards or not. Finally, apart from providing protective comfort to users on the road, this study is also to ensure that the tinted film produced can minimize the impact of accidents. Shattered vehicle mirrors and helmet visors as a result of an accident can inflict more serious injuries on the victim. Therefore, the tinted film used can grip the fragments of the mirror so as not to scatter badly.